Parasitic Array Based Radiation Pattern Reconfigurable Patch Antenna for WLAN Application - Saikia, B.; Borah, K. (Advanced Electromagnetics, 2022)
This article presents a radiation pattern reconfigurable patch antenna using three rectangular parasitic elements for WLAN (5.8 GHz) application. A rectangular driven patch with two parasitic elements placed parallel to both non-radiating edges and the third parasitic element is located on the radiating edge of driven element. The parasitic elements located on non-radiating edges are loaded with shorting posts. The electrical connection between the post and ground plane is controlled by an RF PIN diode switch. Based on switching state (ON/OFF) of the PIN diodes, post loaded parasitic elements, switch their function between director and reflector to produce beam reconfiguration in the proposed antenna. For different switching combinations of the PIN diodes, beam steering directions in H-plane are obtained at 0˚, +50˚, –50˚ for E-plane radiation maximum at +30˚, while fourth beam steering angle is found at ±50˚ with corresponding E-plane radiation maximum at ±40˚. Measured peak gain of the proposed antenna varies between 3.46 dBi and 3.74 dBi for different beam steering modes. With measured resonant frequency around 5.85 GHz throughout the reconfiguration process, the proposed antenna is considered as a potential candidate for WLAN application.